Dollbaby - McNeal, Laura Lane (Pamela Dorman Books/Viking, 2014)
"When Ibby Bell's father dies in a tragic accident in the summer of 1964, her mother unceremoniously deposits Ibby with her eccentric grandmother, Fannie, and throws in her father's urn for good measure. Fannie's Victorian house is like no place Ibby has ever been--and Fannie, who has a tendency to end up in the local asylum every once in a while--is like no one she has ever met. Fortunately, her black cook, Queenie ... and Queenie's feisty daughter Dollbaby take it upon themselves to initiate Ibby into the ways of the South, both its grand traditions and its darkest secrets"--